1994
DOI: 10.1038/jcbfm.1994.41
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Levels Increase in Rat Focal and Global Ischemia

Abstract: Summary: Endothelin-1, a peptide exhibiting extremely potent cerebral vasoactive properties, is elevated in the cerebrospinal fluid after hemorrhagic stroke and impli cated in cerebral vasospasm. The purpose of this study was to determine changes in endothelin in ischemic rat brain by assaying endothelin tissue and extracellular lev els. Immunoreactive endothelin levels in ischemic brain tissue following permanent or transient focal ischemia produced by middle cerebral artery occlusion was deter mined. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(75 citation statements)
references
References 51 publications
2
71
0
1
Order By: Relevance
“…There is good evidence, however, that hypoxia and the peptides vasopressin and endothelin, all factors present during ischemia, stimulate activity of the BBB cotransporter. We have found that vasopressin, which is centrally released during ischemia (Dóczi 1993;Landgraf 1992;Ostrowski et al, 1992;Sorensen et al, 1985) and promotes edema formation (Dickinson and Betz, 1992;Dóczi, 1993;Dóczi et al, 1982Dóczi et al, , 1984Hertz et al, 2000;Rosenberg et al, 1990), is also a potent stimulator of the brain microvascular Na-K-Cl cotransporter (O'Donnell et al, 1995a), as is endothelin, which is also released during ischemia (Barone et al, 1994;Kawai et al, 1996bKawai et al, , 1997Spatz et al, 1997). We have shown that vasopressin stimulates the brain endothelial cotransporter by a V1 vasopressin receptor in a manner involving elevation of intracellular [Ca 2+ ] (O'Donnell et al, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…There is good evidence, however, that hypoxia and the peptides vasopressin and endothelin, all factors present during ischemia, stimulate activity of the BBB cotransporter. We have found that vasopressin, which is centrally released during ischemia (Dóczi 1993;Landgraf 1992;Ostrowski et al, 1992;Sorensen et al, 1985) and promotes edema formation (Dickinson and Betz, 1992;Dóczi, 1993;Dóczi et al, 1982Dóczi et al, , 1984Hertz et al, 2000;Rosenberg et al, 1990), is also a potent stimulator of the brain microvascular Na-K-Cl cotransporter (O'Donnell et al, 1995a), as is endothelin, which is also released during ischemia (Barone et al, 1994;Kawai et al, 1996bKawai et al, , 1997Spatz et al, 1997). We have shown that vasopressin stimulates the brain endothelial cotransporter by a V1 vasopressin receptor in a manner involving elevation of intracellular [Ca 2+ ] (O'Donnell et al, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…It is known that the ET-1 levels in blood and CSF are increased in stroke; this may be further translated to an enhanced receptor-mediated contraction in cerebral arteries [26]. Transcriptional upregulation of ET A and ET B receptors has been reported in rat cerebral arteries after using some injury models like experimental cerebral ischemia and organ culture [10,19,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The endothelin system has been shown to be involved in several pathophysiological conditions, such as atherosclerosis (Iwasa et al 1999), heart failure (Miyauchi and Goto 1999) and ischaemic stroke (Ziv et al 1992;Barone et al 1994;Lampl et al 1997). After middle cerebral artery occlusion (MCAO) in cat, there is an enhanced ET mediated constriction in ischaemic vessels (Patel et al 1996b).…”
Section: Introductionmentioning
confidence: 99%